Description of Parasecia Fernandae sp.N. (trombidiformes: Trombiculidae) and new records of chiggers from rodents in Rio de Janeiro state, Brazil - Jacinavicius, Fernando C.; Bassini-Silva, Ricardo; Amorim, Marinete; Gazêta, Gilberto S.; Siqueira, Liege R.; Welbourn, Warren C.; Barros-Battesti, Darci M. [UNESP] (Tyumen State University, 2018)
In this article, we describe a new species of chiggers, Parasecia fernandae sp.n., and report the presence of Arisocerus hertigi (Brennan et Jones, 1964), Eutrombicula goeldii (Oudemans, 1910), Microtrombicula brachytrichia Brennan, 1971, Parasecia manueli (Brennan et Jones, 1960), Quadraseta brasiliensis Goff et Gettinger, 1989 and Serratacarus dietzi Goff et Whitaker, 1984, for the first time in Rio de Janeiro State. P. manueli is a new record for Brazil. All of these species of chiggers were found parasitizing Nectomys squamipes (Brants, 1827). Besides that, A. hertigi was found on Oxymycterus sp., and S. dietzi—on Cerradomys subflavus (Wagner, 1842).
Keywords: Brazil; Chigger mites; Cricetidae; Ectoparasites; Rio de Janeiro State